THE EFFECT OF WORLD OIL PRICE, INFLATION, TANGIBILITY, PROFITABILITY ON LEVERAGE OF THE JAKARTA ISLAMIC INDEX COMPANY LISTING - Ronaldo Sihombing; Friska Novi Limbong; Justin Novanta Kristian Zai; Dwita Sakuntala; Manda Dwipayani Bhastary (Jurnal Ekonomi, 2023)
The aim of the research is to identify how the influence of world oil prices, inflation, tangibility, profitability on the leverage of the Jakarta Islamic Index listing companies. 49 companies listed on the Jakarta Islamic Index (JII) from 2015-2019. Purposive sampling as the method applied to select samples, and 7 of these companies met the criteria. The research used a quantitative approach. Applying multiple linear regression analysis as an analytical technique. The leverage of the companies listed on the Jakarta Islamic Index is simultaneously influenced by world oil prices, inflation, tangibility and profitability. The findings of this study where world oil prices, inflation, tangibility, profitability partially have no effect on the leverage of the Jakarta Islamic Index listing companies.